Безперервний світловодний контроль температури розплавів в індукційних печах - Zhukov, Leonid; Petrenko, Dmytro (General Energy Institute of the National Academy of Sciences of Ukraine, 2024)
The article is devoted to the question of the most effective for the full use of the induction furnaces technological flexibility continuous temperature control. The aim of the work is to create a light-guide technology for continuous temperature control of the processes of induction melting, treatment and pouring of liquid metal in metallurgy of machine building. The investigations of crucible and channel, melting, holding and pouring induction furnaces from the standpoint of light-guide thermometry have been developed. Materials, designs, as well as technologies of manufacturing, mounting and safe operation of the light-guide and auxiliary devices have also been investigated. Using the results of complex studies, the base light-guide thermometry system, general and particular methods of the light-guide temperature measurements have been developed. On the base of the Huygens construction, as well as the laws of geometric and crystal optics, techniques for calculation of the optical characteristics of the light-guide and focusing devices, as well as schemes of their optical joint have been developed. These techniques increase the metrological characteristics of the light-guide thermometry. Standard construction of the secondary part of thermometry system requires classical pyrometry methods application. These methods are acceptable for continuously operated metallurgical aggregates, where stable emissivity of the light-guide operating end takes place. The secondary part of thermometry system has been modernized in order to widen application field of light-guide thermometry on periodically operated metallurgical aggregates where emissivity of light-guide immersion end randomly changes. Modernized secondary part is purposed for spectral (multicolor) pyrometry methods realization. These methods minimize influence of the instability of emissivity of light-guide immersion end on methodical errors of temperature measurements. Research and industrial exploitation, at domestic and foreign enterprises, have shown obvious metrological advantages of the light-guide thermometry technology in comparison with known solutions. Implementation of the light-guide thermometry systems on induction furnaces has high technical-economic efficiency, including by reduction the spoilage of metal products and resource costs for production.